Cycle Neighbor Polynomial of Graphs - Paul, Annie Sabitha; Pilakkat, Raji (Communications in Mathematics and Applications, 2020)
In this paper, a new univariate graph polynomial called Cycle Neighbor Polynomial \(CN[G;x]\) of a graph \(G\) is introduced. We obtain some interesting properties of this polynomial and compute cycle neighbor polynomial of some specific graphs.